Design considerations for low pressure solar water heating in South Africa - De Meyer, Oelof (Department of Electrical Engineering, 2016)
This thesis investigates the application of solar water heating in South Africa. The solar water heating system investigated work on the thermosiphoning effect or natural convection. An extensive literature study has been undertaken to investigate this phenomena. The three partial differential equations (governing equations) are non-dimensionalized and a similarity solution is applied to obtain two coupled non-linear ordinary differential equations. These equations are then solved in MATLAB to obtain the velocity and temperature profiles. Two scenarios were considered, a vertical wall with a constant wall temperature and a vertical wall with a constant heat flux. LP SWH systems use vacuum tubes to absorb solar radiation and transfer it to the water, which is similar to the vertical wall with a constant heat flux. A simulation model has been developed for a LP SWH system which is able to simulate the system performance for a given geographical location, where the user can specify the system component attributes. Experiments on the system were conducted to validate the simulation model. The simulation model accompanies a 6-Step Design Guide developed to assist the user to design a system able to satisfy the consumer's hot water demand. The 6-Step Design Guide developed can be used in future design considerations for LP SWH systems in South Africa.